Menuju Pendidikan Berkualitas: Upaya Meningkatkan Literasi dan Numerasi di SDN 3 Palembapang Melalui Program Kampus Mengajar Angkatan 6 - Radiansyah, Egi; Resti Umi Melinda; Sarah Aulia Faradina; Ni Made Puspita Sari; Desi Marlina; Dia Septiani Pramesti (STIE Muhammadiyah Kalianda, 2024)
SDN 3 Palembapang faces various challenges in teaching, such as limited availability of reading materials, monotonous teaching methods, and difficulties in understanding literacy and numeracy materials by teachers. To overcome these challenges, various programs were designed, including library empowerment, literacy and numeracy habituation, the adaptation of technology in learning, and the development of students' character through various extracurricular activities. Through a partnership between the school and university students participating in the teaching campus program, the implementation of these programs successfully increased students' interest in reading, literacy, and numeracy skills. The results showed a significant improvement in students' participation in literacy and numeracy activities, as well as more active involvement in learning. Thus, the 6th batch of the teaching campus program made a positive contribution to improving the quality of education at SDN 3 Palembapang